Hạ AD vuông góc BC AB2+IC2=AD2+BD2+ID2+DC2=AC2+IB2 Tương tự , ta có :BC2+IA2=(BD+DC)2+(AD−ID)2=BD2+2BD.DC+DC2+AD2−2AD.ID+ID2=AB2+IC2+2(BD.DC−AD.ID)Xét 2 thằng tam giác đồng dạng BDA IDC =>BD.DC=AD.ID =>Đ.P.C.M p/s: Chiều này off gấp chưa viết đ.c xong :))
Hạ
AD vuông góc
BC AB2+IC2=AD2+BD2+ID2+DC2=AC2+IB2 Tương tự , ta có :
BC2+IA2=(BD+DC)2+(AD−ID)2=BD2+2BD.DC+DC2+AD2−2AD.ID+ID2=AB2+IC2+2(BD.DC−AD.ID)Xét 2 thằng tam giác đồng dạng $BDA
$ ~
$IDC
=> BD.DC=AD.ID
=> Đ.P.C.M$ p/s: Chiều này off gấp chưa viết đ.c xong :))